APLIKASI TELEGRAM (TELE-EDUKASI) DALAM PEMBELAJARAN IPA DI MADRASAH IBTIDAIYAH - Sholikah; Nur Ijazatin Septia (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2019)
Formal education becomes an important role as a forum to develop a lot of learning, be it learning about attitudes or about subjects. One of which the writer will discuss is on Natural Sciences (IPA). Science subjects at the elementary school level are the child's initial process of getting to know the environment in the scope of formal education. Science subjects are important to be introduced to children so that children are able to know what is in their environment. Especially about the life of living things around him. So it takes innovation in the learning process.Telegram is a cloud-based, multi-platform instant messaging service application that is free and non-profit. Telegram Client is available for mobile phone devices (Android, iOS, Windows Phone, Ubuntu Touch) and computer peripheral systems (Windows, OS X, Linux). Users can send messages and exchange photos, videos, stickers, audio, and all types of files or files.The implementation of learning using the telegram application (tele-education) to practice working on science problems shows a gradual increase, namely experiencing an increase in positive things and a decrease in negative things according to the student questionnaire contained in the appendix. Means it can be concluded that the implementation went better and smoothly in each cycle.